Normative Irritability in Youth: Developmental Findings From the Great Smoky Mountain Study - Copeland, William E. (J Am Acad Child Adolesc Psychiatry, 2015)
OBJECTIVE: The goal of this study is to examine the developmental epidemiology of normative irritability and its tonic and phasic components in a longitudinal community sample of youth. METHOD: Eight waves of data from the prospective, community Great Smoky Mountains Study (6,674 assessment of 1,420 participants) were used, covering children in the community aged 9–16 years old. Youth and one parent were interviewed using the Child and Adolescent Psychiatric Assessment to assess tonic (touchy/easily annoyed, irritable mood, angry or resentful) and phasic (temper tantrums or anger outbursts) components of irritability, including frequency, duration, onset, and cross-context variability. RESULTS: At any given point in childhood/adolescence, 51.4% (standard error [SE]=1.4) of participants reported phasic irritability, 28.3% (SE=1.2) reported tonic irritability, and 22.8% (SE=1.1) reported both. These prevalence levels decreased with age but did not vary by sex. The overlap between tonic and phasic irritability was high (OR=5.8, 95% CI, 3.3–10.5, p <.0001), with little evidence of tonic occurring without phasic irritability. Both tonic and phasic irritability predicted one another over time, supporting both heterotypic and homotypic continuity. Low levels of either tonic or phasic irritability increased risk for disrupted functioning including service use, school suspensions, parental burden, and emotional symptoms both concurrently and at one-year follow-up. CONCLUSION: Irritability is relatively common, decreases with age but does not vary by sex, and at almost any level is associated with increased risk of disrupted functioning. Its relative components frequently overlap, although irritable outbursts are more common than irritable mood. Irritability appears to be a high-priority transdiagnostic marker for screening children in need of clinical attention.